1999
DOI: 10.1097/00002030-199909100-00004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of P-glycoprotein function in human lymphocytes and Caco-2 cell monolayers by HIV-1 protease inhibitors

Abstract: We have demonstrated that saquinavir is a substrate for P-gp and that ritonavir, nelfinavir and indinavir modulate P-gp function in both human lymphocytes and Caco-2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 13 publications
1
103
1
1
Order By: Relevance
“…© 2007 American Association for Cancer clincancerres.aacrjournals.org Downloaded from systemic clearance of imatinib in mice (33). Because ritonavir is a known inhibitor of both ABCB1 and ABCG2 (34,35), the current data suggest that modulation of the activity of these transporters in humans would not result in substantially altered exposure to imatinib under steady-state conditions.…”
Section: Discussionmentioning
confidence: 73%
“…© 2007 American Association for Cancer clincancerres.aacrjournals.org Downloaded from systemic clearance of imatinib in mice (33). Because ritonavir is a known inhibitor of both ABCB1 and ABCG2 (34,35), the current data suggest that modulation of the activity of these transporters in humans would not result in substantially altered exposure to imatinib under steady-state conditions.…”
Section: Discussionmentioning
confidence: 73%
“…PIs, however, have minimal effects on CYP2B6. Recent data indicate that most PIs are substrates for the P-gp drug efflux pump, and ritonavir has even been reported to be a potent P-gp inhibitor [21][22][23]. Thus, a multiple dose study on efavirenz and ritonavir in combination in healthy volunteers found ritonavir increased the AUC of efavirenz by 20% [2].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being substrates of CYP, PIs are also substrates and can act as inhibitors of Pglycoprotein, a transmembrane glycoprotein that functions as an energy-dependent efflux pump for a wide variety of structurally unrelated compounds. [53][54][55] Furthermore, the multidrug resistance associated proteins, MRP1 and possibly MRP2, are known to be involved in the disposition of the PIs. [53] These transporter proteins are also involved in drug efflux.…”
Section: Protease Inhibitorsmentioning
confidence: 99%